Pemikiran Fiqh Ahmad Zahro tentang Istinbāṭ Manhajī sebagai Metode Perumusan Hukum Islam - Siti Maryam Qurotul Aini (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2016)
This article examines how Ahmad Zahro establishes the concept of practical use of Istinbāṭ Manhajī in the establishment of Islamic law. In this case, although Zahro claims himself as a follower of a particular school in the field of fiqh, he chooses to use the manhajī method, because this method is seen as being able to provide solutions to contemporary legal problems. The philosophical-juridical foundation built in his fiqh is maqāsid al-sharī'ah and al-maṣlaḥah al-mursalah while considering the level of legal sources as famous among mazhab scholars respectively; al-Qur'ān, al-Sunnah, qiyās, al-istiṣlāḥ, al-'urf, al-istisḥāb, etc., which are formulated as an operational instrument in istinbÃ¢á¹ al-á¸¥ukm. Among Indonesian Muslims, there are differences in approach to the use of istinbāṭ al-ḥukm; NU ulama use qawlī approach, while Muhammadiyah ulama frequently use manhajī approach. Therefore, Zahro specifically believes that what he initiates is an attempt to reconcile approaches of different schools of Muslim law by highlighting Istinbāṭ Manhajī as an option to establish an Islamic law.